Newborn Socialist Things : Materiality in Maoist China - Coderre, Laurence, 1984- (Book collections on Project MUSE., 2021)
"Laurence Coderre explores the material culture of the Chinese Cultural Revolution to show how it paved the way for rampant commodification and consumption in contemporary China."--